Callus Development from Potato (Solanum tuberosum) Stem at Various Concentrations of Benzylaminopurine - Megananda Aprilia; Nintya Setiari; Yulita Nurchayati (Biosaintifika: Journal of Biology & Biology Education, 2022)
Potato has the potential for food diversification.The propagation method in a short period is needed. One of the methods used is plant tissue culture. Benzyl Amino Purine (BAP), determine the success of propagation by tissue culture method. This research aimed to study the use of different BAP concentrations for callus development from stem explants. The explants put on culture medium added by 0, 1, 2, 3 ppm BAP. The development of the stem explant observed every week for a month. The results showed that callus formed in all media. Without BAP treatment, callus were formed after 2 weeks and got browning, then stopped growing. Callus grew and showed differentiation by application of all the BAP concentration. Callus greowth was optimally at 2 ppm BAP treatment. The callus from 1 ppm BAP produced the most number of roots, shoots and leaves than another concentration.  This experiment showed that different BAP concentrations affected callus development of S. tuberosum from stem explant. The conclusion was callus growth has obtained by the treatment of 2 ppm BAP, while the development of callus has obtained on addition of 1 ppm BAP. The novelty of this research is the callus induction method from potato sprout stems grown from potato seeds with plant growth regulators Benzyl Amino Purine. Callus induction method from potato sprout stems grown from potato seeds can be a guide for embryogenic callus induction.